Atlas of Lymphoscintigraphy and Sentinel Node Mapping A Pictorial Case-Based Approach - Mariani, Giuliano.; Manca, Gianpiero.; Orsini, Federica.; Vidal-Sicart, Sergi.; Valdš Olmos, Renato A. (Springer Milan : Imprint: Springer, 2013)
Lymphoscintigraphy is now widely applied for radioguided biopsy of the sentinel lymph node in patients with solid cancers and is considered crucial for adequate planning of oncologic surgery in a growing number of cancers. This atlas presents a collection of richly illustrated teaching cases that demonstrate the clinical relevance and impact of lymphoscintigraphy in different pathologic conditions. The principal focus is on the use of lymphoscintigraphic mapping for radioguided sentinel node biopsy in cutaneous melanoma and cancers at a range of anatomic sites. The most commonly observed lymphoscintigraphic patterns are depicted, and anatomic variants and technical pitfalls of the procedure receive careful attention. The role of tomographic multimodality imaging is also considered. This atlas will be an excellent learning tool for residents in nuclear medicine and other specialists with an interest in the field.